The influence of 17b-estradiol and norethisterone acetate given transdermally and low doses of acetylsalicylic acid on some selected parameters of coagulation and fibrinolysis in menopausal women with some risk factors for coronary heart disease - Stachowiak, Grzegorz; Owczarek, Danuta; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2006)
Aim of study: 1) The impact of transdermal hormone therapy (tHT) on coagulation and fibrinolysis of menopausal women with risk factors for coronary heart disease (CHD). 2) The usefulness of combining this therapy with some anti-thrombotic prophylaxis (low doses of acetylsalicylic acid - ASA). Material and methods: The study group – menopausal women (with 2 or more CHD risk factors) in which tHT composed of 17b-estradiol and NETA (G1, n=22) or the above tHT combined with low ASA doses were administered (ASA) (n=23). Controls were 16 premenopausal women. The following parameters were measured: prothrombin time and index, INR, thrombin time, APTT, fibrinogen, factor VII, vWF, AT III, protein C and S, PAI-1, t-PA, u-PA, TAFI, D-dimers. Treatment duration - 3 months. Results: The therapy influenced mainly some fibrinolytic parameters: in G1 a decrease of PAI-1 from 89.96±52.23 ng/ml to 68.04±31.54 ng/ml (p<0.001) and t-PA from 10.80±5.55 ng/ml to 8.71±3.28 ng/ml (p<0.001) as well as a rise of TAFI from79.57±53.25% to 94.63±42.25% (p<0.01) were noted. In G2 a drop of t-PA from 7.50±5.41 ng/ml to 5.10±3.63 ng/ml (p<0.05), together with a slight drop of TAFI from 102.50±50.53% to 96.40±52.67% were observed (p<0.05). No case of acute cardiovascular event was present during the treatment. Conclusions: 1) Three months of tHT in menopausal women with some CHD risk factors influenced their fibrinolysis in a complex way. 2) It is not advisable to give low ASA doses as anti-thrombotic prophylaxis for this type of hormone therapy.